2013
DOI: 10.1371/journal.pone.0078761
|View full text |Cite
|
Sign up to set email alerts
|

Additive Partitioning of Coral Reef Fish Diversity across Hierarchical Spatial Scales throughout the Caribbean

Abstract: There is an increasing need to examine regional patterns of diversity in coral-reef systems since their biodiversity is declining globally. In this sense, additive partitioning might be useful since it quantifies the contribution of alpha and beta to total diversity across different scales. We applied this approach using an unbalanced design across four hierarchical scales (80 sites, 22 subregions, six ecoregions, and the Caribbean basin). Reef-fish species were compiled from the Reef Environmental Education F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…However species richness did not seem to be regionally affected. This coincides with a recent study at the level of the Caribbean that found that fishing pressure is not important for structuring biodiversity distribution patterns (Francisco‐Ramos & Arias‐González ), although it may affect fish size and abundance, including surgeonfish and parrotfish, in the nsMBRS. Despite this, the low abundances and size structures found here appear to indicate that several environmental factors, not only fishing, are negatively influencing the grazing fish assemblages.…”
Section: Discussionsupporting
confidence: 90%
“…However species richness did not seem to be regionally affected. This coincides with a recent study at the level of the Caribbean that found that fishing pressure is not important for structuring biodiversity distribution patterns (Francisco‐Ramos & Arias‐González ), although it may affect fish size and abundance, including surgeonfish and parrotfish, in the nsMBRS. Despite this, the low abundances and size structures found here appear to indicate that several environmental factors, not only fishing, are negatively influencing the grazing fish assemblages.…”
Section: Discussionsupporting
confidence: 90%
“…). In contrast, Francisco‐Ramos and Arias‐González () investigation of Caribbean reef fishes found larger alpha and smaller beta‐diversity than expected by chance. The authors argued that this resulted from high demographic connectivity in the Caribbean.…”
Section: Discussionmentioning
confidence: 80%
“…A Census of Marine Life study of all Caribbean marine species found species richness to be higher in the Antilles and northern coast of South America, although sampling issues complicated interpretation of these patterns (Miloslavich et al., ). Francisco‐Ramos and Arias‐González () demonstrated that Caribbean marine fish assemblages tend to be more homogeneous than expected by chance and that local species richness (alpha diversity) is a major driver of overall diversity (i.e. gamma diversity) across the Caribbean basin.…”
Section: Introductionmentioning
confidence: 99%